Predictive Factors of Conception and the Cumulative Pregnancy Rate in Subfertile Couples Undergoing Timed Intercourse With Ultrasound - Ahn, So Hyun; Lee, Inha; Cho, SiHyun; Kim, Hye In; Baek, Hye Won; Lee, Jae Hoon; Park, Yun Jeong; Kim, Heeyon; Yun, Bo Hyon; Seo, Seok Kyo; Park, Joo Hyun; Choi, Young Sik; et al. (Frontiers in Endocrinology, 2021)
The aim of this study was to determine predictive factors for pregnancy and assess the cumulative pregnancy rate (CPR) and live birth rate (CLBR) in subfertile couples undergoing timed intercourse (TI) using ultrasound. This retrospective cohort study included 285 women (854 cycles) who started TI with ultrasound. The overall clinical pregnancy rate was 28.1% per couple and 9.4% per cycle. Pregnant women had a higher body mass index (BMI), higher percentage of irregular menstrual cycles, a shorter duration of subfertility, lower serum follicle-stimulating hormone levels, and higher anti-Müllerian hormone levels than non-pregnant women. A longer duration of subfertility (≥24 months vs. <12 months; OR: 0.193; 95% CI: 0.043-0.859) and endometriosis (vs. ovulatory factors; OR: 0.282; 95% CI: 0.106-0.746) as causes of subfertility were unfavorable factors that independently affected clinical pregnancy. In subgroup analysis, old age ≥ 35 years [vs. < 35 years; OR: 0.279; 95% CI: 0.083-0.938), a longer duration of infertility ≥24 months (vs. <24 months; OR: 0.182; 95% CI: 0.036-0.913) and a higher BMI ≥ 25 kg/m2(vs. >25 kg/m2; OR: 3.202; 95% CI: 1.020-10.046) in couples with ovulatory factor and a longer duration of infertility ≥24 months (vs. <24 months; OR: 0.185; 95% CI: 0.042-0.819) in couples with non-ovulatory factors were significant independent predictive factors for pregnancy. No significant differences were found in the cycle characteristics between pregnant and non-pregnant women. The CPR substantially increased during the first three cycles and significantly increased until the sixth cycle. No significant increase was observed in the CPR after the sixth cycle. The CLBRs substantially increased during the first three cycles and significantly increased until the fourth cycle. No significant increase was observed in the CLBRs after the fifth cycle. When comparing CPRs and CLBRs according to subfertile causes, CRPs was significantly different and CLBRs was different with borderline significance. Our findings may indicate that women with a longer duration of subfertility or subfertility due to endometriosis have poor outcomes during TI with ultrasound. Women who failed to achieve conception by the fourth or fifth cycle of TI with ultrasound may be encouraged to consider advancing to the next treatment strategy.